Survey of Guideline Compliance and Attitude Toward Symptom Management in Japanese Intensive Care Units - Shuhei Yamada MS; Hideaki Sakuramoto PhD; Gen Aikawa PhD; Kazuaki Naya MS (SAGE Publishing, 2023)
Introduction The Clinical Practice Guideline for the Management of Pain, Agitation, and Delirium in Adult Patients in the Intensive Care Unit (ICU) was revised in 2018 to include sleep disruption and immobility. Inadequate management of these symptoms can lead to negative consequences. A 2019 survey in Japan found that the guideline was recognized but needed to be consistently implemented. Objective This study aimed to examine compliance with the guideline for symptom management of pain, agitation, delirium, and sleep in Japanese ICUs. Methods This study included all ICUs in Japan and asked one representative from each unit to respond to the web survey from January 2022 to February 2022. Results Of a potential 643 units, 125 respondents from the ICU were included in the analysis (19.4% response rate). Compared to the guideline's recommendations, (a) pain assessment was performed in 86.3% of patients who could self-report, and in 72.0% of those who could not self-report; (b) agitation and sedation assessment was performed in 99% of patients; (c) only 66.1% of nurses reported assessing sleep quality on the units, and 9.1% performed the subjective sleep quality assessment; (d) the use of the recommended risk factor of the delirium assessment tool was low (9.6%). Additionally, according to the survey respondents, contrary to the guideline, many units administered medications to prevent and treat delirium, and approximately 30% used multiple non-drug interventions. The data are expressed as numbers and percentages. Some datasets were incomplete due to missing values. Conclusion Most units used drugs for delirium prevention and treatment, and only a few used non-drug interventions. There is a need to popularize the assessment of sleep and delirium risk factors and use non-drug interventions to promote patient-centered care in the future.